Environmental Concern: Antecedents of Ecotourism Visit Intention with Time Perspective and Destination Image as Determination Variables - Yohan Wismantoro; MG Westri Kekalih Susilowati; Amalia Nur Chasanah; Vincent Didiek Wiet Aryanto (Media Ekonomi dan Manajemen, 2023)
Environmental damage and sustainability become the center of attention along with climate change today. One of the interesting things is the change in behavior in the consumption of products categorized as "green", including in terms of choosing tourism destinations. Environmentally friendly tourism destinations or ecotourism is increasingly becoming an option for those who care about the environment. Ecotourism is also used by many countries, including travel agents, to increase their economic value or profit. This study aims to investigate how the role of Environmental Concern as antecendent of Ecoturism Visit Intention mediates the influence of Future Time perspective and Destination Image toward Ecotourism visit Intention.  This research involved 200 respondents who had visited ecotourism destinations at least twice, which was obtained using a convenience sample approach. The data were analyzed using Structural Equation Modelling (SEM) which were processed using the SmartPLS 4.0 statistical package. The result shows that Future Time perspective and Destination’s Image positively impact Ecotourism Intention.   Future Time perspective and Destination’s Image also influence Ecotourism Intention indirectly through Environmental Concern as the mediating variable. As an implication, the government and travel agents improve service readiness and perception of high-value propositions to develop a better destination image.